5.2.19 Problems 1801 to 1900

Table 5.205: Second order linear ODE

#

ODE

Mathematica

Maple

8795

\[ {}z^{\prime \prime }+3 z^{\prime }+2 z = 24 \,{\mathrm e}^{-3 t}-24 \,{\mathrm e}^{-4 t} \]

8800

\[ {}y^{\prime \prime }+y^{\prime }+y = 0 \]

8801

\[ {}y^{\prime \prime }+y^{\prime }+y = 0 \]

8802

\[ {}y^{\prime \prime }+y^{\prime }+y = 0 \]

8805

\[ {}y^{\prime \prime }-x y^{\prime }-x y-x = 0 \]

8806

\[ {}y^{\prime \prime }-x y^{\prime }-x y-2 x = 0 \]

8807

\[ {}y^{\prime \prime }-x y^{\prime }-x y-3 x = 0 \]

8808

\[ {}y^{\prime \prime }-x y^{\prime }-x y-x^{2}-x = 0 \]

8809

\[ {}y^{\prime \prime }-x y^{\prime }-x y-x^{3}+2 = 0 \]

8810

\[ {}y^{\prime \prime }-x y^{\prime }-x y-x^{4}-6 = 0 \]

8811

\[ {}y^{\prime \prime }-x y^{\prime }-x y-x^{5}+24 = 0 \]

8812

\[ {}y^{\prime \prime }-x y^{\prime }-x y-x = 0 \]

8813

\[ {}y^{\prime \prime }-x y^{\prime }-x y-x^{2} = 0 \]

8814

\[ {}y^{\prime \prime }-x y^{\prime }-x y-x^{3} = 0 \]

8815

\[ {}y^{\prime \prime }-a x y^{\prime }-b x y-c x = 0 \]

8816

\[ {}y^{\prime \prime }-a x y^{\prime }-b x y-c \,x^{2} = 0 \]

8817

\[ {}y^{\prime \prime }-a x y^{\prime }-b x y-c \,x^{3} = 0 \]

8818

\[ {}y^{\prime \prime }-y^{\prime }-x y-x = 0 \]

8819

\[ {}y^{\prime \prime }-y^{\prime }-x y-x^{2} = 0 \]

8820

\[ {}y^{\prime \prime }-y^{\prime }-x y-x^{2}-1 = 0 \]

8821

\[ {}y^{\prime \prime }-y^{\prime }-x y-x^{2}-1 = 0 \]

8822

\[ {}y^{\prime \prime }-2 y^{\prime }-x y-x^{2}-2 = 0 \]

8823

\[ {}y^{\prime \prime }-4 y^{\prime }-x y-x^{2}-4 = 0 \]

8824

\[ {}y^{\prime \prime }-y^{\prime }-x y-x^{3}+1 = 0 \]

8825

\[ {}y^{\prime \prime }-2 y^{\prime }-x y-x^{3}-x^{2} = 0 \]

8826

\[ {}y^{\prime \prime }-y^{\prime }-x y-x^{3}+2 = 0 \]

8827

\[ {}y^{\prime \prime }-2 y^{\prime }-x y-x^{3}+2 = 0 \]

8828

\[ {}y^{\prime \prime }-4 y^{\prime }-x y-x^{3}+2 = 0 \]

8829

\[ {}y^{\prime \prime }-6 y^{\prime }-x y-x^{3}+2 = 0 \]

8830

\[ {}y^{\prime \prime }-8 y^{\prime }-x y-x^{3}+2 = 0 \]

8831

\[ {}y^{\prime \prime }-y^{\prime }-x y-x^{4}+3 = 0 \]

8832

\[ {}y^{\prime \prime }-y^{\prime }-x y-x^{3} = 0 \]

8833

\[ {}y^{\prime \prime }-x y-x^{3}+2 = 0 \]

8834

\[ {}y^{\prime \prime }-x y-x^{6}+64 = 0 \]

8835

\[ {}y^{\prime \prime }-x y-x = 0 \]

8836

\[ {}y^{\prime \prime }-x y-x^{2} = 0 \]

8837

\[ {}y^{\prime \prime }-x y-x^{3} = 0 \]

8838

\[ {}y^{\prime \prime }-x y-x^{6}-x^{3}+42 = 0 \]

8839

\[ {}y^{\prime \prime }-x^{2} y-x^{2} = 0 \]

8840

\[ {}y^{\prime \prime }-x^{2} y-x^{3} = 0 \]

8841

\[ {}y^{\prime \prime }-x^{2} y-x^{4} = 0 \]

8842

\[ {}y^{\prime \prime }-x^{2} y-x^{4}+2 = 0 \]

8843

\[ {}y^{\prime \prime }-2 x^{2} y-x^{4}+1 = 0 \]

8844

\[ {}y^{\prime \prime }-x^{3} y-x^{3} = 0 \]

8845

\[ {}y^{\prime \prime }-x^{3} y-x^{4} = 0 \]

8846

\[ {}y^{\prime \prime }-x^{2} y^{\prime }-x^{2} y-x^{2} = 0 \]

8847

\[ {}y^{\prime \prime }-x^{3} y^{\prime }-x^{3} y-x^{3} = 0 \]

8848

\[ {}y^{\prime \prime }-x y^{\prime }-x y-x = 0 \]

8849

\[ {}y^{\prime \prime }-x^{2} y^{\prime }-x y-x^{2} = 0 \]

8850

\[ {}y^{\prime \prime }-x^{2} y^{\prime }-x^{2} y-x^{3}-x^{2} = 0 \]

8851

\[ {}y^{\prime \prime }-x^{2} y^{\prime }-x^{3} y-x^{4}-x^{2} = 0 \]

8852

\[ {}y^{\prime \prime }-\frac {y^{\prime }}{x}-x y-x^{2}-\frac {1}{x} = 0 \]

8853

\[ {}y^{\prime \prime }-\frac {y^{\prime }}{x}-x^{2} y-x^{3}-\frac {1}{x} = 0 \]

8854

\[ {}y^{\prime \prime }-\frac {y^{\prime }}{x}-x^{3} y-x^{4}-\frac {1}{x} = 0 \]

8855

\[ {}y^{\prime \prime }-x^{3} y^{\prime }-x y-x^{3}-x^{2} = 0 \]

8856

\[ {}y^{\prime \prime }-x^{3} y^{\prime }-x^{2} y-x^{3} = 0 \]

8857

\[ {}y^{\prime \prime }-x^{3} y^{\prime }-x^{3} y-x^{4}-x^{3} = 0 \]

8859

\[ {}y^{\prime \prime }+c y^{\prime }+k y = 0 \]

8861

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

8862

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

8863

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

8864

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

8865

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

8866

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

8867

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

8868

\[ {}y^{\prime \prime }+y = \sin \left (x \right ) \]

8869

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right ) \]

8870

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right ) \]

8871

\[ {}y^{\prime \prime }+y^{\prime }+y = \sin \left (x \right ) \]

8873

\[ {}x^{4} y^{\prime \prime }+x^{3} y^{\prime }-4 x^{2} y = 1 \]

8874

\[ {}x^{4} y^{\prime \prime }+x^{3} y^{\prime }-4 x^{2} y = x \]

8875

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-4 y = x \]

8888

\[ {}4 x^{2} y^{\prime \prime }+y = 8 \sqrt {x}\, \left (\ln \left (x \right )+1\right ) \]

8953

\[ {}\frac {x y^{\prime \prime }}{1-x}+y = \frac {1}{1-x} \]

8954

\[ {}\frac {x y^{\prime \prime }}{1-x}+x y = 0 \]

8955

\[ {}\frac {x y^{\prime \prime }}{1-x}+y = \cos \left (x \right ) \]

8956

\[ {}\frac {x y^{\prime \prime }}{-x^{2}+1}+y = 0 \]

8957

\[ {}y^{\prime \prime } = \left (x^{2}+3\right ) y \]

8960

\[ {}y^{\prime \prime }+20 y^{\prime }+500 y = 100000 \cos \left (100 x \right ) \]

8961

\[ {}y^{\prime \prime } \sin \left (2 x \right )^{2}+y^{\prime } \sin \left (4 x \right )-4 y = 0 \]

8963

\[ {}y^{\prime \prime }+2 x y^{\prime }+\left (x^{2}+1\right ) y = 0 \]

8964

\[ {}y^{\prime \prime }+2 \cot \left (x \right ) y^{\prime }-y = 0 \]

8965

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

8966

\[ {}4 x^{2} y^{\prime \prime }+\left (-8 x^{2}+4 x \right ) y^{\prime }+\left (4 x^{2}-4 x -1\right ) y = 4 \sqrt {x}\, {\mathrm e}^{x} \]

8967

\[ {}x y^{\prime \prime }-\left (2+2 x \right ) y^{\prime }+\left (x +2\right ) y = 6 \,{\mathrm e}^{x} x^{3} \]

8977

\[ {}y^{\prime \prime }+2 y^{\prime }-24 y = 16-\left (x +2\right ) {\mathrm e}^{4 x} \]

8978

\[ {}y^{\prime \prime }+3 y^{\prime }-4 y = 6 \,{\mathrm e}^{2 t -2} \]

8981

\[ {}x y^{\prime \prime }-\left (2 x +1\right ) y^{\prime }+\left (1+x \right ) y = 0 \]

9072

\[ {}y^{\prime \prime } = 0 \]

9073

\[ {}{y^{\prime \prime }}^{2} = 0 \]

9074

\[ {}{y^{\prime \prime }}^{n} = 0 \]

9075

\[ {}a y^{\prime \prime } = 0 \]

9076

\[ {}a {y^{\prime \prime }}^{2} = 0 \]

9077

\[ {}a {y^{\prime \prime }}^{n} = 0 \]

9078

\[ {}y^{\prime \prime } = 1 \]

9079

\[ {}{y^{\prime \prime }}^{2} = 1 \]

9080

\[ {}y^{\prime \prime } = x \]

9081

\[ {}{y^{\prime \prime }}^{2} = x \]

9082

\[ {}{y^{\prime \prime }}^{3} = 0 \]

9083

\[ {}y^{\prime \prime }+y^{\prime } = 0 \]